The Spectrum of von Willebrand’s Disease - Bowie, E. J Walter; Didisheim, P; Thompson, J. H, Jr.; Owen, C. A, Jr. (Thrombosis and Haemostasis, 1967)
Patients (from 5 kindreds) with variants of von Willebrand’s disease are described. In one kindred the depression of factor VIII was moderate (20 to 40% of normal) and transfusion of 500 ml of normal plasma led to an increase higher than anticipated and to an almost normal level of factor VIII 17 to 24 hrs later. This represents the usual type of von Willebrand’s disease.In the second kindred the concentration of factor VIII was less than 2 % of normal in the son and daughter, who had severe bleeding and hemarthroses.The third kindred was characterized by reduction of factor VIII and a long bleeding time as well as by a serum defect in the thromboplastin-generation test comparable to that seen in patients with hemophilia B, yet with normal levels of factors IX, X, and VII. The severity of the serum defect, the positive result with the Rumpel-Leede test, and the reduced platelet activity in the thromboplastin-generation test are all compatible with the diagnosis of thrombopathy or ‘‘thrombopathic hemophilia.” In two other kindreds, one patient had a long bleeding time and normal levels of factor VIII and another had a normal bleeding time and decrease of factor VIII. The last patient had the type of response to transfusion usually seen in von Willebrand’s disease.In four kindreds, platelet adhesiveness in vivo was found to be strikingly abnormal (virtually absent).It would appear, therefore, that von Willebrand’s disease forms a spectrum, and whether the kindreds reported simply reflect variations of a single genetic disease state or represent separate entities will be answered only by clarification of the underlying etiology of that disease.